2004
DOI: 10.1146/annurev.biophys.33.110502.140414
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Water in Protein-DNA Recognition

Abstract: Is it by design or by default that water molecules are observed at the interfaces of some protein-DNA complexes? Both experimental and theoretical studies on the thermodynamics of protein-DNA binding overwhelmingly support the extended hydrophobic view that water release from interfaces favors binding. Structural and energy analyses indicate that the waters that remain at the interfaces of protein-DNA complexes ensure liquid-state packing densities, screen the electrostatic repulsions between like charges (whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
165
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(171 citation statements)
references
References 144 publications
4
165
0
2
Order By: Relevance
“…This mechanism is especially intriguing because sequence dependent hydration effects are already known to play a role in sequence dependent DNA-protein interactions (43) and RNA folding (44). It would be reasonable to assume that hydration effects also play a role in homology-dependent dsDNA/ dsDNA interaction and attractive to think that such diverse situations all have a common underlying physical basis.…”
Section: Discussionmentioning
confidence: 99%
“…This mechanism is especially intriguing because sequence dependent hydration effects are already known to play a role in sequence dependent DNA-protein interactions (43) and RNA folding (44). It would be reasonable to assume that hydration effects also play a role in homology-dependent dsDNA/ dsDNA interaction and attractive to think that such diverse situations all have a common underlying physical basis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been demonstrated that residues and bases not directly in contact with each other also can play important roles in protein-DNA recognition via various mechanisms, e.g. by water-mediated contacts 14 or sequence-dependent, binding-induced conformational changes and distortions. 15,16 Because of the great diversity of protein-DNA binding patterns and modes, identifying DNAbinding proteins based on structural features is a challenging task, especially if the goal is to devise a method that is not limited to a particular family of DNA-binding proteins, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…2b). The role of these water molecules in protein-DNA recognition and complex formation is diverse as reviewed previously (Jayaram and Jain 2004). We classified the hydrogen bonded interfacial water molecules into those only contacting the DNA or those facilitating water-mediated contacts between amino acids and the DNA sugar-phosphate backbone or bases.…”
Section: Recovery Of Water-mediated Hydrogen Bonded Contactsmentioning
confidence: 99%
“…For protein-DNA interactions in particular, water molecules are involved in diverse tasks such as screening for favorable DNA interaction sites, stabilizing complex formation and facilitating specific interactions (Janin 1999;Jayaram and Jain 2004;Reddy et al 2001;Schwabe 1997). For example, the specificity in the trp repressor-operator complex is governed nearly exclusively by water-mediated amino acid to base interactions (Otwinowski et al 1988;Shakked et al 1994).…”
Section: Introductionmentioning
confidence: 99%